Summer bottom oxygen depletion dynamics and the associated physical structure in the Bohai Sea - Zhang, Jing; Yang, Wei; Song, Guisheng; Zhang, Haiyan; Zhao, Liang (Frontiers in Marine Science, 2023)
Summertime oxygen depletion has been more and more frequently observed in the bottom water of the Bohai Sea in the last decade. Based on comprehensive hydrography and microstructure measurements in summer in the Bohai Sea, the physical structure and bottom dissolved oxygen (DO) dynamics were investigated. The study area is characterized by strong tidal currents and obvious horizontal temperature and DO gradients in the bottom boundary layer. The strong tidal forcing induces large near-bottom turbulent kinetic energy dissipation rates (ϵ 5 × 10-5 W kg-1) which can be well parameterized by the law of the wall. Tidal horizontal advection effects dominate the short-term variations of bottom hydrography. Although the residual current is in a near-perpendicular direction with the horizontal DO gradient ( 94°), the horizontal residual DO transport was calculated to be 67.4 mg m-2 d-1 which is 33% of the magnitude of sediment oxygen demand. During the observation period, we observed an intense high-turbidity event leading to a severe drawdown of near-bottom DO concentration (0.16 mg L-1) in 1.5 hours. The DO consumption rate due to this event was then estimated to be 33.3 g m-2 d-1 (1.39 g m-2 h-1) which is two orders of magnitude larger than the sediment oxygen demand. Rapid DO consumption can be induced by the great increase in bioavailable surface area in bottom water and seabed when benthic organic matter is resuspended. This process should be incorporated into the coupled physical-biogeochemical model to improve accuracy in simulating DO depletion.